A study of the effectiveness of credit subsidies: evidence from a panel of Italian firms - Rapisarda, G; Patacchini, E (University of Oxford, 2003)
Credit subsidies in targeted industrial sectors or geographical areas are a primary mechanism of industrial and redistributive policy throughout the world. Using a unique panel of bank-firm relationships, we study the impact of interest-rate subsidies on the total amount of borrowing and on the average cost of borrowing for subsidised firms. Even though they seem to promote the rise of new bank firm relationships, subsidies have a relatively small effect on the total amount of borrowing when granted to existing clients. We also find evidence of a spillover effect of subsidies on non-subsidised interest rates, which is suggestive of possible rent-seeking activities undertaken by banks and their targeted borrowers. The size of the subsidy, the bank's local market power, her informational advantage and the length of the bank-client relationship are found to be important determinants of the spillover effect.